(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Wireless devices increase the comfort of human life by reducing labor work and data reading accuracy. Wireless device transfer data though allotted spectrum or free available spectrum. An IOT device has limited resources to establish communication between source and destination. So paper has work on cognitive IOT network which depends on algorithms that can sense spectrum efficiently and route data. Paper has summarized various researcher work done for blank spectrum sensing in cognitive IOT network which may be co-operative or non co-operative in nature. Further some of network routing issues were explained that were directly or indirectly depends on hardware limitation, algorithm computation, etc. Routing algorithms were also list in the work which was used by scholars to resolve different network issues